Электрофизические и сорбционные свойства торфяного композита - Наумова Л. Б.; Горленко Н. П.; Саркисов Ю. С.; Карташова А. А. Анна Александровна; Жуйкова А. В.; Рехтин А. Ф. (2014, 2014)
Заглавие с экрана